Extensive Myiasis Infestation over a Malignant Lesion in Maxillofacial Region Report of Cases - Santosh Kumar Yadav, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Extensive Myiasis Infestation over a Malignant Lesion in Maxillofacial Region Report of Cases